Out of Syria: Mobile Media in Use at the Time of Civil War. Issue 7 (2nd July 2016) - Rohde, Markus; Aal, Konstantin; Misaki, Kaoru; Randall, Dave; Weibert, Anne; Wulf, Volker
ABSTRACT: Social media usage during the recent uprisings in Arab countries has gained increasing attention in human–computer interaction research. This study adds to these insights by providing some findings on the use of information and communications technology (ICT), specifically mobile media, by opposition forces and political activists during the Syrian civil war. The presented study is based on 17 interviews with Syrian FSA fighters, activists, and refugees. A first analysis showed evidence for some very specific use patterns during wartime (compared to media usage of political activists under less anomic conditions). The study also describes a fragmented telecom infrastructure in Syria: government-controlled regions offer fairly intact infrastructures while rebel-controlled regions have been cut off from telephone and Internet. Moreover, the central and very critical role of mobile video for documenting, mobilization, and propaganda is discussed.